THE ECONOMIC VALUE OF PADDY FIELD BASED ON ITS FACULTIES TO SUPPORT LAND PRODUCTIVITY IN LOWOKWARU SUBDISTRICT, MALANG, EAST JAVA - Rina Suprihati (Socio-Economics/Agribusiness Department, 2017)
: Paddy fields commonly possesses intrinsic natural processes and external benefits that support land productivity. Soil fertility which shown by nutrient contents (Nitrogen, phosporous, potassium and organic matters) gives evidence of the existence of natural processes that occur within the soil that will be lost when land conversion happens. Similarly the external benefit of paddy fields as container of domestic waste compost will be lost too due to the land conversion. These functions and benefits are very important but are not appreciated by society. Giving economic values to paddy fields based on these two faculties will inform the society how valuable paddy fields are as natural resources. The economic valuation method used in this reserch is the Replacement Cost Method (RCM) with mathematical formula as follows NELSsFPUH = (UN x Pn + UP x Pp + UK x Pk+ UBO x PBO) x A for economic value of paddy field as provider of nutrients contents (N, P, K) and organic matters; and NELSPK = (WK/KK) x PK x A for economic value of paddy field as compost container. The research was taken place in 6 sub-subdistricts in Lowokwaru Subdistrict with 205 hectares of paddy fields. The economic value of paddy field is about Rp 133,31 billions for economic value of paddy field as provider of nutrients contents (N, P, K) and organic matters; and Rp 7,76 billions for economic value of paddy field as compost container. For both faculties the average economic value Rp 688,18 million per hectare. Paddy fields in Lowokwaru Subdistricts are very feasible to be protected from conversion due to its satisfactory soil fertility and its potential to be increased, thus it is able to maintain land productivity. Therefore, it is very reasonable to call pady fields as productive open green space in which economic and social activities can be developed